Partial Volumes of Phosphatidylcholines and Vitamin E: α‑Tocopherol Prefers Disordered Membranes - DiPasquale, Mitchell; Nguyen, Michael H. L.; Pabst, Georg; Marquardt, Drew (The journal of physical chemistry. B, 2022)
Despite its discovery over 95 years ago, the biological and nutritional roles of vitamin E remain subjects of much controversy. Though it is known to possess antioxidant properties, recent assertions have implied that vitamin E may not be limited to this function in living systems. Through densitometry measurements and small-angle X-ray scattering we observe favorable interactions between α-tocopherol and unsaturated phospholipids, with more favorable interactions correlating to an increase in lipid chain unsaturation. Our data provide evidence that vitamin E may preferentially associate with oxygen sensitive lipidsan association that is considered innate for a viable membrane antioxidant.